2021
DOI: 10.3989/mc.2021.13520
|View full text |Cite
|
Sign up to set email alerts
|

NORM waste, cements, and concretes. A review

Abstract: The use of industrial waste and/or by-products as alternative sources of raw materials in building materials has become standard practice. The result, more sustainable construction, is contributing to the institution of a circular economy. Nonetheless, all necessary precautions must be taken to ensure that the inclusion and use of such materials entail no new health hazard for people or their environment. Due to the processes involved in generating industrial waste/by-products, these alternative or secondary m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 85 publications
0
11
0
Order By: Relevance
“…Their natural radioactivity, as such, should be determined to ensure their safety and to avoid any health and environmental issues. Constituents identified as NORMs include FA, GGBS, ACS, FS, SF, RM, volcanic tuff, and WG, to name a few [201]. Their radioactivity is determined from the concentration of natural radionuclide content, mainly 226 Ra (radium series), 232 Th (thorium series) and 40 K (potassium) [202].…”
Section: Health and Environmental Aspectsmentioning
confidence: 99%
“…Their natural radioactivity, as such, should be determined to ensure their safety and to avoid any health and environmental issues. Constituents identified as NORMs include FA, GGBS, ACS, FS, SF, RM, volcanic tuff, and WG, to name a few [201]. Their radioactivity is determined from the concentration of natural radionuclide content, mainly 226 Ra (radium series), 232 Th (thorium series) and 40 K (potassium) [202].…”
Section: Health and Environmental Aspectsmentioning
confidence: 99%
“…The equipment used enables standard measurements of sample permeability for gas and tests including the effect of gas slip (19) so that even at low speeds, the gas flowing through the porous material behaves in accordance with Darcy's law. The obtained permeability coefficient can also be converted into filtration coefficient (k) for water (expressed in m/s) using the Equation [2]: [2] where: K P is the permeability coefficient (mD), γ is the specific gravity of liquid (N/cm 3 ) and η is the dynamic viscosity of liquid (Pa•s).…”
Section: The Determination Of Physical and Chemical Parameters Of Bricksmentioning
confidence: 99%
“…The waste from hard coal mining accumulated in landfills is a considerable burden for the local natural environment. The scale and extent of this phenomenon depends on many factors, including the amount and type of the waste, as well as its chemical composition and the content of heavy metals, the concentration of natural radionuclides, radon exhalation and other physical properties (2).…”
Section: Introductionmentioning
confidence: 99%
“…Very few studies have been conducted on alkaline-activated cement and concretes (geopolymers) radiological behaviour [14,[36][37][38], but none whatsoever on the hybrid cement pastes and the relationship with their microstructure. Deploying a new method developed by the authors that uses solid 5 cm cubic specimens, the present research confirmed the existence of such a relationship in hybrid (70 wt% OPC + 30 wt% FA) cement pastes.…”
Section: Introductionmentioning
confidence: 99%